2021
DOI: 10.1111/jog.14727
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for velamentous umbilical cord insertion in singleton pregnancies after assisted reproductive technology

Abstract: Aim Assisted reproductive technology (ART) is gaining popularity worldwide. However, it is associated with increased incidence of velamentous umbilical cord insertion (VCI) in the placenta, resulting in adverse perinatal outcomes. This study aimed to identify the risk factors that might affect the incidence of VCI in pregnancies after ART treatment. Methods We retrospectively analyzed the records of 906 singleton pregnancies via ART; all women delivered in our facility. Three ART‐related variables and infant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 27 publications
(60 reference statements)
0
17
0
Order By: Relevance
“…The study selection scheme is illustrated in Figure 1 . Overall, 1463 studies were examined, and 16 studies (37,128 ART pregnancies and 1,597,784 non-ART pregnancies) met the inclusion criteria for the descriptive analysis [ 7 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. As the two studies reported by Ebbing et al [ 33 , 35 ] used overlapping data (same database), the outcome of interest was different between them.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study selection scheme is illustrated in Figure 1 . Overall, 1463 studies were examined, and 16 studies (37,128 ART pregnancies and 1,597,784 non-ART pregnancies) met the inclusion criteria for the descriptive analysis [ 7 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. As the two studies reported by Ebbing et al [ 33 , 35 ] used overlapping data (same database), the outcome of interest was different between them.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias assessment for the included studies is presented in Supplemental Table S2 . Of those ( n = 16), a possible moderate publication bias (moderate quality) in 10 studies [ 7 , 29 , 30 , 31 , 33 , 34 , 35 , 36 , 37 , 38 ] and severe publication bias (low quality) in the other six studies [ 25 , 26 , 27 , 28 , 32 , 39 ] were observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions in the reproductive process during the most critical and vulnerable period of life formation, i.e., fertilization and early embryonic development, will more or less affect the development of gametes and embryos. And it may be stably transmitted during cell lysis and embryonic development, thereby affecting the health of offspring and even the next generation [ 6 , 7 ]. ART obtains more high-quality oocytes through controlled superovulation.…”
Section: Introductionmentioning
confidence: 99%